Investigating circulating miRNA in transition dairy cows: What miRNAomics tells about metabolic adaptation - Veshkini, Arash; Hammon, Harald Michael; Lazzari, Barbara; Vogel, Laura; Gnott, Martina; Tröscher, Arnulf; Vendramin, Vera; Sadri, Hassan; Sauerwein, Helga; Ceciliani, Fabrizio (Frontiers in Genetics, 2022)
In the current study, we investigated dairy cows' circulating microRNA (miRNA) expression signature during several key time points around calving, to get insights into different aspects of metabolic adaptation. In a trial with 32 dairy cows, plasma samples were collected on days -21, 1, 28, and 63 relative to calving. Individually extracted total RNA was subjected to RNA sequencing using NovaSeq 6000 (Illumina, CA) on the respective platform of IGA Technology Services, Udine, Italy. MiRDeep2 was used to identify known and novel miRNA according to the miRbase collection. Differentially expressed miRNA (DEM) were assessed at a threshold of fold-change > 1.5 and false discovery rate < 0.05 using the edgeR package. The MiRWalk database was used to predict DEM targets and their associated KEGG pathways. Among a total of 1692 identified miRNA, 445 known miRNA were included for statistical analysis, of which 84, 59, and 61 DEM were found between days -21 to 1, 1 to 28, and 28 to 63, respectively. These miRNA were annotated to KEGG pathways targeting the insulin, MAPK, Ras, Wnt, Hippo, sphingolipid, T cell receptor, and mTOR signaling pathways. MiRNA-mRNA network analysis identified miRNA as master regulators of the biological process including miR-138, miR-149-5p, miR-2466-3p, miR-214, miR-504, and miR-6523a. This study provided new insights into the miRNA signatures of transition to the lactation period. Calving emerged as a critical time point when miRNA were most affected, while the following period appeared to be recovering from massive parturition changes. The primarily affected pathways were key signaling pathways related to establishing metabolic and immune adaptations.